GLOBAL EDUCATIONAL STANDARDS AND NATIONAL CULTURAL IDENTITY: THE DIALECTICS OF CONTRADICTIONS - O'ralova Gulyuz Orifjon qizi (Bright Mind Publishing, 2025)
This article analyzes the dialectics of contradictions between globalization processes in education and the preservation of national cultural identity. The article analyzes the contradictions between global educational standards and national culture, the issues of universalization and localization in education, as well as the risk of losing national characteristics in education systems. The article also emphasizes the need to harmonize global and national values in education, which will play an important role in creating sustainable and just education systems in the future.
Keywords: Global education standards, national cultural identity, dialectics of contradictions, universalization, localization, PISA study, globalization.